Characteristics of music performance anxiety among undergraduate music students: A systematic review - Barros, S. (2022)
Music performance anxiety (MPA) is described as a persistent apprehension that compromises performative skills both in solo and group performances. The aim of this systematic review was to discuss an overview of research articles addressing the characteristics of MPA as experienced by undergraduate music students. The search was undertaken in the databases Web of Science, PubMed, Scopus and Eric; of 1526 articles identified by the search keywords, 43 were selected for review through the PRISMA protocol. The study types included cross-sectional, experimental, longitudinal, descriptive, questionnaire survey, qualitative study, exploratory and retrospective follow-up designs. This review evidences the diversity of the contexts and topics addressed by current research, namely issues of prevalence, predictors of anxiety/risk factors, relationship between flow experience (FE) and MPA, and coping with MPA, adopting psychological, cognitive, physiological and behavioral perspectives. Notwithstanding, the review has also identified a lack of qualitative and longitudinal studies, studies on institutional teaching contexts, and of larger and more representative participant samples, which could promote a better understanding of the etiology of MPA among students attending higher education.